The birth of New Indonesia (six monhs PRRI) : commemoration monograph, genesis and development of the Revolutionary Government of the Republic of Indonesia. (Genève : PRRI Mission in Europe, 1958)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Indonesië